ANALISIS KEPATUHAN TERHADAP PRINSIP KERJA SAMA GRICE DALAM KOMIK SUNDA SI MAMIH AN ANALYSIS OF GRICE’S COOPERATIVE PRINCIPLE IN SUNDANESE’S COMIC “SI MAMIH” - Hera Meganova Lyra; Gugun Gunardi; Teddi Muhtadin (Jurnal KATA: Penelitian tentang Ilmu Bahasa dan Sastra, 2020)
Si Mamih is a Sundanese comic character created by the cartoonist Edyana Latief. This obese female cartoon character, identical with black spotted shirt and crested hair, may deliver a comical communication that brings smiles and laughs as the Sundanese people character’s assertion that are fond of humor. Evidently, in delivering her humor, Si Mamih does not always disobey the cooperative principle. There is obedience toward Grice’s theory performed by Si Mamih. This obedience can be observed in maxims of quality, quantity, relevance and manner. The obedience of Si Mamih toward the cooperative principle is intentionally performed by its cartoonist creator as a uniqueness of delivering creativity and imagination which bring smiles and laughs.